Temperature development and damage rates of onion thrips - Jamieson, L.E.; Chhagan, A.; Griffin, M. (New Zealand Plant Protection, 2012)
Bulb damage caused by onion thrips (Thrips tabaci Thysanoptera Thripidae) is a serious problem in New Zealand stored export onions Understanding the relationships between insect development rates temperature and damage potential is critical to effective pest management by targeting fewer pesticide applications Thrips development (egg to adult) was monitored daily on leek leaves onion leaves or onion bulb discs at constant and variable temperatures Development rates were not significantly different on different substrates but survival was lower on onion bulbs Total development time (egg to adult) ranged from 511 days at 12C to 103 days at 30C Lower development temperature thresholds ranged from 73C for pupae to 91C for eggs Accumulation of 221 degreedays above 81C was required to complete development The temperature development model accurately predicted development time of onion thrips under variable temperature conditions At 21C adults and larvae caused an average of 201 and 107 mm2 of feeding damage to onion bulbs per day respectively